Leveraging WMI scripting using Windows Management Instrumentation to solve Windows management problems - Lissoir, Alain (Boston : Digital Press, 2003)
Leveraging WMI Scripting is the second in a series of two books dedicated to WMI. Understanding WMI Scripting (ISBN 1-55558-266-4), Lissoir's first book, explained to Windows Administrators the various WMI scripting techniques and manageability capabilities of this new Windows Server 2003 platform. Illustrated with hundreds of scripts and detailed tables, the book explained the underlying technology and how WMI can be put to work. Lissoir focused not only on WMI programming aspects for developers but on how administrators can use what is available in Windows for their admin work. If you've had significant WMI experience, or have read Lissoir's first book, you are ready to apply your WMI knowledge to any technology that interfaces with WMI. Leveraging WMI Scripting continues the presentation of WMI begun in Understanding WMI Scripting. In this new volume, we dive deeper into WMI to understand the manageable entities of the Windows world. Lissoir offers a structured description of the most important WMI providers available from Windows NT 4.0 to Windows Server 2003 (including Windows 2000 and Windows XP). This covers the WMI management of the Windows Registry, Active Directory, SNMP, the Resultant Set Of Policies (RSOP), and the Volume Shadow Service to name a few. This discussion leverages the information on building real-world scripted management solutions presented in Lissoir's first book. Like the first volume, Leveraging WMI Scripting is based on an important concept: "learning by practice." Leveraging WMI Scripting addresses the most advanced topics so that you can exploit the features of various WMI interfaces to manage the components in a real-world environment. WMI is a critical topic under Windows Server 2003, so this book provides real added value to every Windows administrator. Shows you how to extract data from applications, understand what's really happening on your servers, and get real work done Provides hundreds of usable scripts to use in everyday solutions for network performance and security Offers practical and straightforward advice that any enterprise Windows administrator can learn from.
The Windows WMI Providers Discovery; The Win32 Providers; The WMI Providers; WMI Security Scripting; The Optional Windows Components and Application WMI Providers; A Look Into the Future of WMI Scripting.
Includes index.
Keywords: Microsoft Windows (Computer file).; Operating systems (Computers).; Programming languages (Electronic computers).; Microsoft Windows (Computer file).; Electronic books